BEHAVIOR AND EMOTION MODULATION DEFICITS IN PRESCHOOLERS AT RISK FOR BIPOLAR DISORDER. Issue 5 (17th February 2015) - Tseng, Wan‐Ling; Guyer, Amanda E.; Briggs‐Gowan, Margaret J.; Axelson, David; Birmaher, Boris; Egger, Helen L.; Helm, Jonathan; Stowe, Zachary; Towbin, Kenneth A.; Wakschlag, Lauren S.; Leibenluft, Ellen; Brotman, Melissa A.
Abstract : Background: Bipolar disorder (BD) is highly familial, but studies have yet to examine preschoolers at risk for BD using standardized, developmentally appropriate clinical assessment tools. We used such methods to test whether preschoolers at familial risk for BD have more observed difficulty modulating emotions and behaviors than do low‐risk preschoolers. Identification of emotional and behavioral difficulties in at‐risk preschoolers is crucial for developing new approaches for early intervention and prevention of BD. Methods: Using the standardized disruptive behavior diagnostic observation schedule (DB‐DOS) protocol for preschoolers, we compared 23 preschoolers ( M age : 4.53 ± 0.73 years; 18 males) with a first‐degree relative with BD to 21 preschoolers ( M age : 4.65 ± 0.84 years; 11 males) without a family history of BD. We characterized psychopathology in this sample using the Preschool Aged Psychiatric Assessment and behavioral and emotional problems using the Child Behavior Checklist. Results: High‐risk preschoolers demonstrated significantly more intense, pervasive, and clinically concerning problems in anger modulation and behavior dysregulation on the DB‐DOS than the low‐risk group. High‐risk relative to low‐risk preschoolers, were also more likely to have maternal‐reported anxiety and oppositional defiant disorders and internalizing and externalizing problems. Conclusions: Clinically concerning problems in anger modulation and behavior regulation, measured during standardized laboratory observation, differentiate preschoolers at high familial risk for BD from those at low risk. Investigation in a large longitudinal sample is critical for replication and for determining whether these observed behavioral differences can be reliably used as prodromal indicators of mood disorders.